Legal certainty gaps in cessie notification: a doctrinal comparison of the indonesian civil code and ojk consumer protection standards - Beny Anang Prihantoro; Ema Rahmawati; Gatot Yulianto (Indonesian Institute For Counseling, Education and Therapy, 2026)
This study analyzes legal-certainty gaps in bank notification of the assignment of receivables (cessie) by comparing Article 613 of the Indonesian Civil Code with Articles 50 and 52 of Financial Services Authority Regulation Number 22 of 2023. It employs doctrinal legal research using statutory, conceptual, and case approaches. Primary legal materials were selected because they directly regulate assignment, banking prudence, consumer protection, electronic evidence, and personal data. Five anonymized case illustrations were purposively included because they describe notification, receipt, unilateral transfer, or third-party collection. Analysis used a norm-comparison matrix covering the agreed channel, proof of receipt, timing and confirmation, information completeness, and sanctions. The results identify ambiguity in the agreed means of correspondence, the absence of an explicit proof-of-receipt duty, inconsistent evidentiary standards between Articles 50 and 52, and insufficient operational rules on confirmation and documentation. The study proposes a technology-neutral, evidence-based notification standard that protects consumers while supporting prudential banking and legal certainty.